EUTHANASIA DALAM PANDANGAN ETIS TEOLOGI KRISTEN: ANTARA KASIH DAN PENDERITAAN - Litri Yerisa Eribka; Melan; Yohana Katerina Tinopi; Sarmaui (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study examines euthanasia from the ethical point of view of Christian theology, with a primary focus on the relationship between love and suffering. Through a theological-ethical qualitative approach and a literature study method, this study analyzes Christian theological views on life, human dignity, and terminal suffering in moral and spiritual contexts. The results of the study show that in Christian theology, life is understood as a divine gift from God that cannot be terminated by humans, because only God has sovereignty over life and death. True love (agape) is interpreted as empathetic companionship through palliative care and pastoral service, not as an act to end suffering. Suffering in the context of the Christian faith is seen as having spiritual value that can deepen man's faith and relationship with God. Thus, euthanasia, whether active or passive, cannot be ethically-theologically justified. The Church and Christian institutions are expected to strengthen the ministry of love, spiritual consolation, and the development of ethical and pastoral education that affirms the sacred value of life and respect for human dignity in the midst of terminal suffering